The Effect of Social Presence on the Trust and Repurchase of Social Commerce Tiktok Shop Users - Thesia, Fandhy Achmed Belkaoui; Aruan, Daniel Tumpal Hamonangan (International Journal Labs, 2023)
This comprehensive study delves into the fascinating realm of social presence (SP) and its pivotal role in shaping consumer behavior within the TikTok Shop ecosystem. The investigation meticulously dissects three pivotal facets of SP's influence: SP emanating from the platform itself, SP stemming from the perceptions of other users, and the dynamic SP experienced through interactions on TikTok LIVE. Furthermore, the study meticulously scrutinizes the extent to which various features within the domain of social commerce act as moderators, shaping the influence of each SP factor. To meticulously probe these aspects, the research employs advanced structural equation modeling techniques, illuminating the intricate relationships at play. A substantial dataset of 200 survey responses was thoughtfully collected through an online survey. The compelling findings unveil that not one, but two distinct social presence characteristics wield a significant impact on consumer trust. Notably, even after the meticulous control of social commerce features, one pivotal component of SP emerges as a trust-building catalyst. Consequently, this engenders a heightened likelihood of repeat purchases among consumers navigating the TikTok Shop landscape. This study, by meticulously dissecting the multifaceted interplay of SP and social commerce features, provides valuable insights into enhancing consumer trust and fostering repeat engagement within TikTok Shop, thereby offering actionable guidance for businesses operating in this burgeoning social commerce sphere.